Supercritical fluid extract of Angelica sinensis promotes the anti-colorectal cancer effect of oxaliplatin - Hao, Doudou; Liu, Jia; Guo, Ziyou; Chen, Jiajia; Li, Tingting; Li, Xin; Mei, Kai; Wang, Lingmin; Wang, Xinyi; Wu, Qing (Frontiers in Pharmacology, 2022)
Oxaliplatin-based chemotherapy regimens are recommended for patients with advanced colorectal cancer (CRC). However, oxaliplatin (OXA) can cause toxic side effects at the recommended dosage. Therefore, it is necessary to find new drug candidates that can synergize with OXA and thereby lower the OXA dose while still maintaining its efficacy. Angelica sinensis, as a common drug in Traditional Chinese Medicine, has been demonstrated significant anti-colorectal cancer effect in modern pharmacological studies. The active ingredients in Angelica sinensis could be effectively extracted by supercritical fluid extract. In this study, the supercritical fluid extract of Angelica sinensis (A-SFE) was obtained by a stable extraction process and it was chemically characterized by GC/MS. The anti-cancer effect of A-SFE when applied individually was explored in vitro through MTT, scratch and transwell assay. The effect of A-SFE on CRC cells under the influence of tumor-associated macrophages (TAMs) was explored by co-culture model. The results showed that A-SFE could inhibit the viability, metastasis and invasion of HCT116 cells especially under the influence of TAMs. When 20~100 μg/mL of A-SFE and 8~64 μg/mL of OXA were used in combination in HCT116 cells, synergistic or additive effects were shown in different concentration combinations. The CT26 syngeneic mouse model was used to explore the anti-colorectal cancer effect of OXA combined with A-SFE in vivo. The tumor volume, expression levels of Ki67, MMP9 and CD206 in the OXA + A-SFE group were less than those in the OXA group. In conclusion, A-SFE has the potential to become an adjuvant drug for OXA in the treatment of CRC, which provides new strategies for anti-colorectal cancer research.